SISTEM PENGUKURAN KEPUASAN PASIEN TERHADAP PELAYANAN KLINIK NYAI WALIDAH - Nugraha, Hafiz; Kurniawansyah, Kevin (LPPM Universitas Muhammadiyah Jambi, 2022)
In the era of globalization, excellent service is the main element in hospitals and health units, including health services provided by clinics. Likewise in the health service industry, such as the Nyai Walidah clinic. Almost all health units are required to provide health services that meet optimal service standards. To be able to gain an advantage in the competition, every company must be able to meet customer satisfaction, with a strategy that is in accordance with the services it offers. As for customer satisfaction, the company can fulfill one of them through the quality of its service. Patients will feel satisfied if the performance of the health services obtained equals or exceeds their expectations. The level of patient satisfaction is very important and is closely related to the level of patient return so that this can be used as an indicator of the quality of health services. Therefore, this study aims to measure patient satisfaction with Nyai Walidah's clinical services using the waterfall method. Which produces a satisfaction measurement system to assess the level of satisfaction of visiting patients and as an evaluation material for the performance of health services so that components can be identified that must be maintained and improved by the Nyai Walidah clinic.